2020
DOI: 10.1002/pat.4964
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic toughening of iso‐polypropylene with high‐density polyethylene and polycyclooctene synthesized by ROMP

Abstract: A series of different molecular weight Polycyclooctene(PCOE) rubber were synthesized via ROMP with G2 catalyst and Iso‐polypropylene (iPP), PCOE and high density polyethylene (HDPE) blends were prepared by micro twin‐screw extruder. The effects of PCOE molecular weight and content were investigated by studying the thermal, rheological and mechanical properties of the blends. We observed that the low molecular weight PCOE promoted the dispersion of HDPE, and as the molecular weight and content of PCOE rising, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The result suggests that vHDPE has a better compatibility with ethylene-based olefin block copolymer (C1). According to the literature, such decrease in interfacial tension as well as the increase in adhesive energy during the melt blending and extrusion process is evidence of good adhesion as well as core-shell formation, in which the dispersed phase is encapsulated by compatibilizer [32][33][34]. In this case, dispersed vPP in vHDPE matrix is encapsulated only by the ethylene-based olefin block copolymer (C1).…”
Section: Prediction Of Morphology By Contact Angle Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…The result suggests that vHDPE has a better compatibility with ethylene-based olefin block copolymer (C1). According to the literature, such decrease in interfacial tension as well as the increase in adhesive energy during the melt blending and extrusion process is evidence of good adhesion as well as core-shell formation, in which the dispersed phase is encapsulated by compatibilizer [32][33][34]. In this case, dispersed vPP in vHDPE matrix is encapsulated only by the ethylene-based olefin block copolymer (C1).…”
Section: Prediction Of Morphology By Contact Angle Measurementsmentioning
confidence: 98%
“…The encapsulation of PE in PP matrix by propylene-based olefin block copolymer [26,32,33], ethylene propylene random copolymers (EPR) [13,37] and styrene-ethylen-butylene-stryrene triblock copolymers (SEBS) [27] has been reported in the literature. However, the encapsulation of vPP in vHDPE matrix by propylene-based olefin block copolymer (C2) or ethylene-propylene-random copolymers (C3 and C4) or styrene-ethylene-butylene-styrene triblock copolymers (C5 and C6) has not been found in this study.…”
Section: Prediction Of Morphology By Contact Angle Measurementsmentioning
confidence: 99%
“…Vranjes and Rek observed a similar trend using 5 and 7 wt % of NORDEL IPNDR 4520 (EDPM, DuPont) in 40:60 HDPE/iPP blends . More recently, the He group prepared a series of polycyclooctenes (PCOE, Figure D) by ring-opening metathesis polymerization (ROMP) of cyclooctene and utilized them as compatibilizers for 10:90 HDPE/iPP blends . They observed that the minimum amount of compatibilizer was 10 wt % to improve the blend’s ε B (633%).…”
Section: Review Of Blendsmentioning
confidence: 76%
“…183 More recently, the He group prepared a series of polycyclooctenes (PCOE, Figure 7D) by ring-opening metathesis polymerization (ROMP) of cyclooctene and utilized them as compatibilizers for 10:90 HDPE/iPP blends. 195 They observed that the minimum amount of compatibilizer was 10 wt % to improve the blend's ε B (633%). It was also noted that a relatively high molar mass PCOE (M n > 120 kg/mol) was essential to improve the mechanical properties of the blends, which relates to its essential role in forming entanglements and tie chains.…”
Section: Hdpe/ipp Blendsmentioning
confidence: 99%
“…In order to overcome this issue, several strategies have been adopted to increase its toughness 2,10‐15 . It is generally accepted that blending PHBV with flexible polymers 16 or plasticizers is an effective approach for its toughening. Wang et al 12 blended thermoplastic polyurethane (TPU) to toughen PHBV.…”
Section: Introductionmentioning
confidence: 99%